Paroxysmal complete atrioventricular block in pediatric heart transplant recipients following cardiac catheterization: A case series. (10th May 2018) - Magnetta, Defne A.; Feingold, Brian; Beerman, Lee B.; Blasiole, Brian; Arora, Gaurav
Abstract: Late‐onset paroxysmal AVB has been described as a rare complication after HT and has been associated with AR or CAV. We describe 4 pediatric HT recipients who developed paroxysmal AVB hours after routine cardiac catheterization in the absence of AR, CAV, or underlying conduction system disease. Four pediatric HT recipients who were >1 year post‐transplant had episodes of paroxysmal AVB hours after surveillance cardiac catheterization with EMB. Telemetry demonstrated high‐grade block, ranging from 2:1 AVB to complete AVB without ventricular escape for several seconds. None of the patients had significant AR or rapidly progressive CAV. Supplemental testing did not reveal underlying conduction system disease. Three of the 4 patients received permanent pacemakers, although subsequent interrogations showed minimal ventricular pacing. These pediatric HT recipients had paroxysmal AVB hours after cardiac catheterization in the absence of significant AR, CAV, or underlying conduction system disease. Subsequent pacemaker interrogations showed minimal ventricular pacing, suggesting these were isolated episodes. These cases suggest that mechanisms in addition to AR and CAV may cause paroxysmal AVB in pediatric HT recipients, warranting further investigation.